Perancangan Kualitas Layanan Berdasarkan Perspektif Islam Di Rumah Sakit Umum Daerah (RSUD) - Nugraha, Nugraha (ITB AAS INDONESIA Surakarta, 2024)
The problem in this study is the existence of complaints from patients who use hospital services against the management of the X Regional General Hospital (RSUD) in the city of Bandung, obtained from the results of a preliminary survey. This problem needs to be solved by designing Islamic service quality measurements so as to increase hospital patient satisfaction. The main objective of this study is to design service quality based on Islamic law at the X Regional General Hospital in the city of Bandung. The method used in this research is the Service Quality (SERVQUAL) method and Islamic law. From the research results obtained from the validity testing results of 27 statements declared valid because the value of R count is greater than the value of R table and the results of reliability testing obtained a value of 0.917, then the measuring instrument used is reliable. Based on the servqual model used, there are several indicators from each part of the SERVQUAL element that must be made critical improvements by the RSUD to improve the quality of their services. It is hoped that this research can improve patient satisfaction with the quality of hospital management service.